Advanced containerization : using Docker and Linux for an in-depth exploration of container concepts and functionalities - Bowler, Talon (O'Reilly, 2016)
"This video is targeted at developers that are comfortable with Linux, have some experience working with containers and want to advance their understanding of containerization and the ecosystem surrounding it. The course focuses on the behind the scenes details that one must take into account when designing new applications around containers or when containerizing a legacy application. Knowing basic Docker functionality (how to run containers, how to view running containers, etc.) will be helpful as most of the commands demonstrated will interact with Docker."--Resource description page.